Peer support workers as a bridge: a qualitative study exploring the role of peer support workers in the care of people who use drugs during and after hospitalization - Robin Lennox; Larkin Lamarche; Tim O'Shea (BMC, 2021)
Abstract Background To describe the key qualities and unique roles of peer support workers in the care of people who inject drugs during and after hospitalization. Methods We conducted a qualitative study. Key stakeholders were recruited including: people who use drugs who had been hospitalized, healthcare team members, peer support workers, and employers of peer support workers. Data were collected from 2019 to 2020 using semi-structured interviews that were audio-recorded, transcribed, and analyzed thematically. Results Fourteen participants were interviewed: 6 people who use drugs who had been hospitalized, 5 healthcare team members, 2 peer support workers, and 1 employer of peer support workers. At the core of the data was the notion of peer workers acting as a bridge. We found four themes that related to functions of this bridge: overcoming system barriers, advocacy, navigating transitions within the healthcare system, and restoring trust between HCPs and PWUD. We found two themes for building a strong bridge and making the role of a peer support worker function effectively (training and mentorship, and establishing boundaries). We found three themes involving characteristics of an effective peer worker (intrinsic qualities, contributions of shared experiences, and personal stability). Conclusion Peer support workers are highly valued by both people who use drugs and members of the healthcare team. Peer support workers act as a bridge between patients and healthcare providers and are critical in establishing trust, easing transitions in care, and providing unique supports to people who use drugs during and after hospitalization.